2017
DOI: 10.1590/s1677-5538.ibju.2016.0494
|View full text |Cite
|
Sign up to set email alerts
|

Implantation of a biodegradable rectum balloon implant: Tips, Tricks and Pitfalls

Abstract: Introduction:A rectum balloon implant (RBI) is a new device to spare rectal structures during prostate cancer radiotherapy. The theoretical advantages of a RBI are to reduce the high radiation dose to the anterior rectum wall, the possibility of a post-implant correction, and their predetermined shape with consequent predictable position.Objective:To describe, step-by-step, our mini-invasive technique for hands-free transperineal implantation of a RBI before start of radiotherapy treatment.Materials and Method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 21 publications
0
22
0
Order By: Relevance
“…An appropriate expansion to the system would be to include NTCP models for these types of toxicities. The possible complications after placement of the IRS (pain, rectal perforation) were not taken into account, as the risk of these factors is low (<5%) [27], and are not yet fully described. Furthermore, the nomograms on which the NTCP model is based are from 2002 to 2004, where now outdated dose delivery techniques were conformal.…”
Section: Discussionmentioning
confidence: 99%
“…An appropriate expansion to the system would be to include NTCP models for these types of toxicities. The possible complications after placement of the IRS (pain, rectal perforation) were not taken into account, as the risk of these factors is low (<5%) [27], and are not yet fully described. Furthermore, the nomograms on which the NTCP model is based are from 2002 to 2004, where now outdated dose delivery techniques were conformal.…”
Section: Discussionmentioning
confidence: 99%
“…However, the method presented here has the potential to identify patients with this SNP who could be treated safely with radiotherapy after placement of an IRS. This would be beneficial, since placing an IRS is less invasive and has a very low to no impact on the quality of life, especially in comparison with surgery [8]. This would also be beneficial for patients who don't want an operation or who are not candidates for surgery.…”
Section: Discussionmentioning
confidence: 99%
“…The implantable rectum spacer (IRS) is a device developed to spare the rectum by increasing the distance between the anterior rectal wall and the prostate, thus reducing the overlap between the rectal wall and the high-dose region [6][7][8][9]. Recent studies have shown that this device significantly reduces the dose in the rectum, thus reducing the risk of complications, for approximately 20% of the patients [5].…”
Section: Introductionmentioning
confidence: 99%
“…The RBI has some practical advantages [ 9 ]. First of all postimplant correction of the RBI position is possible; if the RBI is dispositioned, it can be easily deflated and replaced, whereas liquid spacers (PEG hydrogels, hyaluronic acid, human collagen) do not permit any correction once being injected [ 9 , 12 ]. In addition, a chemical reaction is required to occur in PEG hydrogels, which limits the implantation time.…”
Section: Discussionmentioning
confidence: 99%
“…An RBI was implanted in these patients between the prostate and the anterior rectal wall 7–10 days prior to the start of EBRT. The injection technique has been previously described in detail [ 12 ]. A short general anesthesia is preferred at our department.…”
Section: Methodsmentioning
confidence: 99%